The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1186/s12916-022-02371-8
|View full text |Cite
|
Sign up to set email alerts
|

Ten years of tracking mental health in refugee primary health care settings: an updated analysis of data from UNHCR’s Health Information System (2009–2018)

Abstract: Background This study examines mental, neurological, and substance use (MNS) service usage within refugee camp primary health care facilities in low- and middle-income countries (LMICs) by analyzing surveillance data from the United Nations High Commissioner for Refugees Health Information System (HIS). Such information is crucial for efforts to strengthen MNS services in primary health care settings for refugees in LMICs. Methods Data on 744,036 M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 52 publications
(51 reference statements)
1
10
0
Order By: Relevance
“…In line with previous research [ 68 ] the interviews with females showed scepticism toward mental health professionals unfamiliar with their background. This might illuminate recent research showing that healthcare service utilization rates among refugees in camps are particularly low for common mental disorders [ 11 ]. Nonetheless, more females than males mentioned mental health care services as help seeking source for psychological distress.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…In line with previous research [ 68 ] the interviews with females showed scepticism toward mental health professionals unfamiliar with their background. This might illuminate recent research showing that healthcare service utilization rates among refugees in camps are particularly low for common mental disorders [ 11 ]. Nonetheless, more females than males mentioned mental health care services as help seeking source for psychological distress.…”
Section: Discussionmentioning
confidence: 57%
“…Health systems in camps must manage a wide range of mental, neurological and substance use problems [ 8 ]. While access to health services may often be limited, cultural variations in explanations of illnesses and preferred coping strategies and help-seeking paths may also constitute significant barriers to providing mental health services to refugees [ 9 11 ]. As Rasmussen, Katoni [ 12 ] point out, to treat, one must communicate, and to communicate well, one must understand the local explanatory models (EMs).…”
Section: Introductionmentioning
confidence: 99%
“…Fine et al ’s retrospective analysis4 examines the extent to which mental health (particularly mental, neurological and substance use (MNS)) service utilisation has changed over the 10-year analysis period. The analysis included data from 175 refugee camps in 24 countries, where the number of MNS visits was compared with camp population, in relation to gender, age group and country.…”
Section: Methodsmentioning
confidence: 99%
“…Over the years, attention to mental health and psychosocial support in emergencies has grown remarkably 4 . Mental health has now become a routine part of primary health care interven tions in humanitarian settings 5 . The accumulation of evidence around a suite of brief scalable psychological interventions tai lored to the needs of people affected by emergencies has fueled optimism that we can effectively treat common mental health conditions with relatively modest means 6,7 .…”
Section: A Minimum Service Package (Msp) To Improve Response To Menta...mentioning
confidence: 99%
“…Social determinants of health include not only individual characteristics (e.g., income, highest completed edu cation) but also structural determinants and social arrangements (e.g., class location). Recent studies suggest that important rela tionships between genetic risk and social context may be present even at the neighborhood level (e.g., collective efficacy) 5 , and the influence of sociocultural context is likely to be greater at higher levels (e.g., racialized minority vs. dominant majority; nations with plentiful vs. scarce resources). Consequently, GWEIS limited to the narrow range captured by standard biological measures of the "exposome" will also be rather uninformative in this regard.…”
mentioning
confidence: 99%